PERGANTIAN MANAJEMEN SEBAGAI PEMODERASI PENGARUH UKURAN KAP DAN AUDIT TENURE PADA AUDITOR SWITCHING - Pradnyani, Ni Pt Intan; Latrini, Made Yeni (E-Jurnal Akuntansi, 2017)
Auditor switching divided into mandatory and voluntary based on the reasons for the change of auditors. The purpose that researcher want to achieve in this research is to know the effect of firm size and audit tenure that moderated by changes of management on auditor switching. The scope of this research was banking companies listed on the Indonesian Stock Exchange 2011 – 2015. This research is used logistic regression as analysis technic. The results of the research found that the firm size is negatively effect the auditor switching, while auditing tenure and management changes had no negative effect on the auditor switching. After moderated by management changes, it was found that the changes of management is able to amplify the effect of firm size on the auditor switching. While the audit tenure moderate, the changes of management are disable to strengthen the effect of audit tenure on auditor switching.
Keywords: audit tenure, auditor switching, voluntary, firm size.